An Approach to Evaluate Mountain Forest Protection and Management as a Means for Flood Mitigation - Rüegg, Janine; Moos, Christine; Gentile, Alice; Luisier, Gilles; Elsig, Alexandre; Prasicek, Günther; Otero, Iago (Frontiers in Forests and Global Change, 2022)
We are of the opinion that environmental policies that are based on scientific knowledge at the time they are established need to be revisited in terms of the current knowledge and the effectiveness of these policies in protecting or promoting a particular ecosystem service. Here we use the first Swiss Federal Forest Law (1876) as a case example, which was established to protect mountain forests as a natural means of protection against natural hazards, particularly floods. We briefly summarize the current relevant scientific knowledge on i) reasons for reforestation in mountains and how the law may have contributed, ii) forest effects on hydrological regimes and their protection service against floods, and iii) other watershed changes affecting both reforestation and the forest-runoff interaction. We then present insights from a case study on the Upper Rhone catchments, which lead us to develop a methodological approach based on interdisciplinary collaboration among social and natural sciences to gain the needed data to answer the question of whether a forest protection law can serve as a means of flood protection. Specifically, we found that a data interpolation method is key to answering this question given data are at different scales and resolutions and suggest modeling to fill gaps. Such methods and collaborations are key for basing environmental laws and policies in current scientific knowledge and effectively manage ecosystems and their services.